The orphan collector - Wiseman, Ellen Marie (Kensington Books, 2020)
"In the fall of 1918, thirteen-year-old German immigrant Pia Lange longs to be far from Philadelphia's overcrowded streets and slums, and from the anti-German sentiment that compelled her father to enlist in the U.S. Army, hoping to prove his loyalty. But an even more urgent threat has arrived. Spanish influenza is spreading through the city. Soon, dead and dying are everywhere. With no food at home, Pia must venture out in search of supplies, leaving her infant twin brothers alone... Since her baby died days ago, Bernice Groves has been lost in grief and bitterness. If doctors hadn't been so busy tending to hordes of immigrants, perhaps they could have saved her son. When Bernice sees Pia leaving her tenement across the way, she is buoyed by a shocking, life-altering decision that leads her on a sinister mission: to transform the city's orphans and immigrant children into what she feels are "true Americans." As Pia navigates the city's somber neighborhoods, she cannot know that her brothers won't be home when she returns. And it will be a long and arduous journey to learn what happened, even as Bernice plots to keep the truth hidden at any cost. Only with persistence, and the courage to face her own shame and fear, will Pia put the pieces together and find the strength to risk everything to see justice at last."--